Academic Procrastination in College Students: Do Academic Burnout and Smartphone Addiction Matter? - Sujadi, Eko; Ahmad, Bukhari (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
Academic procrastination is a behavior commonly exhibited by college students. The objective of this study was to investigate the impact of academic burnout and smartphone addiction on academic procrastination, both partially and simultaneously. A cross-sectional survey design was employed, involving 214 students from a state university in Jambi Province, Indonesia. We adapted the Short Form of the Academic Procrastination Scale, the Oldenburg Burnout Inventory – Student Version (OLBI-S), and the Smartphone Addiction Scale - Short Version (SAS-SV) for data collection. The data were analyzed using simple and multiple linear regression. The findings suggest that academic burnout and smartphone addiction are predictors of academic procrastination, with a stronger effect observed from smartphone addiction on academic procrastination. This research has significant implications for addressing academic procrastination by reducing academic burnout and smartphone addiction. Interventions targeting self-regulation could also be pursued, as they have proven effective across all variables examined. The implementation of guidance and counseling programs in higher education institutions should be optimized to cultivate an effective student lifestyle.